Pengaruh Likuiditas, Profitabilitas, Leverage dan Kepemilikan Institusional Terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Pemoderasi - Ananda Mutiara Syahputri; Desi Ika; Yani Suryani (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This research aims to determine the effect of Liquidity, Profitability, Leverage and Institutional Ownership on firm value with Dividend Policy as a moderating variable. This type of research is a quantitative. the population this study are all manufacturing companies listed on the Indonesia Stock Exchange in 2018-2023. The sampling techniques used purposive sampling method with samples of 40 companies. The analysis technique used is Moderated Regression Analysis (mra). The results of this research indicates that liquidity had a negative effect on firm value, profitability, and institutional ownership had a positive effect on firm value, leverage had no effect on firm value, devidend policy didnot moderate the effect of liquidity and leverage on firm value, devidend policy moderate the effect of profitability and institutional ownership on firm value in manufacturing companies listed on the indonesia stock exchange in period of 2018-2023